From plot to landscape scale: linking tropical biodiversity measurements across spatial scales. Issue 3 (13th March 2009) - DeFries, Ruth; Rovero, Francesco; Wright, Patricia; Ahumada, Jorge; Andelman, Sandy; Brandon, Katrina; Dempewolf, Jan; Hansen, Andrew; Hewson, Jenny; Liu, Jianguo
Abstract : Quantitative measurements of changes in tropical biodiversity are sparse, despite wide agreement that maintaining biodiversity is a key conservation goal. Pan‐tropical networks to systematically measure plot‐level biodiversity are currently being developed to close this gap. We propose that a key component of such networks is the monitoring of human activities at broader scales around plots, to enable interpretation of biodiversity trends. This monitoring goal raises questions about the spatial extent and variables needed to capture interactions between human activities and biodiversity at multiple scales. We suggest a pragmatic approach to delineate and monitor a "zone of interaction" around biodiversity measurement sites to bridge across these scales. We identify the hydrologic, biological, and human interactions that connect local‐scale measurements with broader‐scale processes. We illustrate the concept with case studies in the Udzungwa Mountains in Tanzania and Ranomafana National Park in Madagascar; however, the framework applies to other biodiversity measurement sites and monitoring networks as well.